Addressing Competency Gaps in Aviation Maintenance Education: Lessons from the Philippine Experience - Dela Peña, Arthur; Rutao, Meredith; Tiglao, Harold (Journal of Technical Education and Training, 2025)
This study investigates competency gaps in the Aircraft Maintenance Technology (AMT) program of the Philippine State College of Aeronautics (PhilSCA), assessing how well the curriculum aligns with international aviation standards, including the International Civil Aviation Organization’s (ICAO) Annex 1 on personnel licensing, the European Union Aviation Safety Agency’s (EASA) Part 66 on aircraft maintenance licensing, and the Philippine Civil Aviation Regulations (PCAR) Part 3 governing approved training organizations. Employing a convergent mixed-methods design, the study collected data from 85 purposively selected participants, including graduates, industry professionals, and educators, between January and March 2024. Data collection involved surveys, semi-structured interviews, and curriculum document analysis to evaluate training effectiveness and graduate readiness. Results show strong curriculum alignment in foundational topics such as propulsion systems and safety documentation. However, significant gaps were identified in advanced diagnostics, avionics systems, composite materials, and essential soft skills such as communication and teamwork. Graduates who completed On-the-Job Training (OJT) in airline environments demonstrated higher job readiness than those trained in more minor Maintenance, Repair, and Overhaul (MRO) facilities. The study underscores the need to adopt competency-based education (CBE), standardize OJT placements, and deepen industry-academic partnerships. Recommendations include integrating certification pathways, expanding practical training, and establishing continuous curriculum review processes. By analyzing the Philippine experience, this study offers actionable insights for developing countries. These findings inform scalable reforms toward a globally aligned aviation workforce.